The effect of antioxidants in Ehrlich Ascites Cancer - Yılmaz, Seher; Tokpınar, Adem; Eroğlu, Ece; Ateş, Şükrü; Zahid, Rabbia; Avnioğlu, Seda; Bozkurt, Özlem; Nisari, Mehtap (Cellular and Molecular Biology, 2021)
A fundamental goal in molecular oncology is to unravel the underlying mechanisms which cause the cell transformation. In line with this approach, genome-wide functional screening approaches have revealed exciting insights into heterogeneous nature of cancer. Rapidly expanding horizons of research have unraveled myriad of pathways which play instrumental role in carcinogenesis and metastasis. Oxidative stress has also been reported to be significantly involved in cancer onset and progression. In line with this approach, oxidative stress modulating chemicals have always been sharply divided into antioxidants and oxidative stress-inducing agents. Conceptual and experimental advancements have enabled us to critically analyze full potential of these two different groups of chemicals in cancer chemoprevention. Different antioxidants are currently being analyzed in different phases of clinical trials. Although it has been reported in the literature that antioxidant supplements reduce tumor cells in some tumors or cause volume reduction in solid tumor sizes, there is no definite consensus. Therefore, an antioxidant supplement guideline based on more detailed clinical research and as a result of these is needed to achieve the best care for cancer patients and to avoid risky treatments for cancer patients.